Penyelesaian Perkara Tindak Pidana Narkotika dengan Pelaku Anak Melalui Pendekatan Restorstive Justice - Safira, Ilma Aulia; Susila, Muh Endriyo (Universitas Muhammadiyah Yogyakarta, 2023)
Perpetrators of narcotics crimes are not only adults, but can also be children. Handling of children who commit narcotics crimes refers to the provisions of Law Number 35 of 2009 concerning Narcotics, however the criminalization process is still based on the provisions of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This aims to provide protection for children who are in conflict with the law. This research aims to analyze the resolution of narcotics crime cases by children using a restorative justice approach at the Batang Police Station. The type of research carried out is normative-empirical legal research. The results of the research show that the resolution of narcotics crime cases with child perpetrators at the Batang Police has been carried out in accordance with Perpol Number 8 of 2021, Law Number 35 of 2009, and Law Number 11 of 2012. The position of the concept of restorative justice is seen as standing alone as alternative case resolution, so that solutions to narcotics crimes committed by children can be sought through restorative justice by fulfilling material and formal requirements. While handling narcotics crime cases committed by children, Batang Police Investigators act as facilitators and mediators.